Predictive factors for recurrent febrile seizures in children - Pengekuten Marudur; Elisabeth Herini; Cahya Dewi Satria (Paediatrica Indonesiana, 2012)
Background Oneô€¡third of children who experience febrile seizureshave a recurrence, '\.Vith rates of75% in the first year, and 90% mthinthe second year following the first febrile seizure. Predictive factorsfor recurrent febrile seizures have been reported in studies from othercountries, but there have been few of these studies in Indonesia.Objective To determine predictive factors for the recurrence offebrile seizures in children.Methods Children w i t h firstô€¡time febrile seizures wereprospectively followed up, for at least 12 months. Subjects wererecruited consecutively from August 2008 to April 20 1 0 from twohospitals in Yogyakarta and one hospital in Klaten. We monitoredrecurrences of febrile seizure by telephone or home visits to parentsevery 3 months. Time to first recurrence of febrile seizures wasanalyzed using the Cox regression model.Results T here were 196 children v,ith firstô€¡time febrile seizures whocompleted the follow up. Recurrent seizures were observed in 56children (28.6%). Me811 follow up time was 21.7 (SD 6.6) months.Temperature of <40"C at the time of seizure (RR=2.29, 95%CI 135to 3.89, P=0.OO2), history of febrile seizures in firstô€¡degree relatives(RR=330, 95%CI 1.25 to 8.08, P<O.OOl), age at first febrile seizureof <12 months (RRô€¢2.40, 95%CI 1.42 to 4.06, Pô€¢O.OOI) andduration of fever before the seizure of:51 hour (RR=4.62, 95%CI:1.35 to 15.80, P=0.015) were significantly associated v,ith recurrenceof febrile seizures. Furthermore, Cox regression analysis revealedthat the age of < 12 months, history of febrile seizures in firstô€¡degreerelatives and temperature of < 40" C were significantpredictive factorsfor the recurrence of febrile seizures.Conclusion Age at first seizure of < 12 months, history of febrileseizures in firstô€¡degree relatives, and seizure v,ith temperature of<40"C were independent predictive factors for recurrent febrileseizures in children. [Paediatr lndones. 2012;52:317,23].